Peran Kelas Ibu Balita Terhadap Praktik Pemberian ASI Ekslusif - Luluk Hidayah; Devi Rosita (Dian Nuswantoro Semarang, 2018)
Toddler’s Mother Class has an important role in improving the coverage ofexclusive breast feeding. The purpose of this study was to describe the role of theToddler’s Mother Class with exclusive breast feeding practice in Public HealthCenter of Godong I.This study used qualitative methods with snowball sampling techniques. Theinformant of the study are toddler’s mother who have a child aged 6-12 months withtotal informant are ten informant. Collecting data technique with in-depth interviewsand used interview guidelines.The results showed that implementation of Toddler’s Mother Class was donethree times a year by the facilitator, consists of a village midwives, public healthcenters midwives, and a nutritionist or dental expert or infectious disease controlofficer. Source of funding the activities derived from Special Operational Assistance(BOK), media health promotion used a sheet back, and targets were not grouped byage, but focused on toddlers who haved growing hibicus problems. Most ofinformants have knowledgeable about exclusive breast feeding and have agreed togive exclusive breast feeding. However, only a portion (50%) the informant canprovide exclusive breast feeding to her baby, because the lack of support from thehusband and family.Toddler’s Mother Class at Public Health Center of Godong I wasimplemented in all of the village, but there was still mother of a baby who does notprovide exclusive breast feeding.